Urban development - Andrian, Peter; Donato, Aaron Firth; Auliffe, Mark; Classroom Video Pty. Ltd. (Bendigo, Vic. : Classroom Video, 2006)
This program examines the geographical processes involved, the perceptions of various groups and the responses, decision-making and management required for successful urban development
Writer, Simon Garner ; camera, Nik Hayward...[et al.] ; production manager, Edwina Baden-Powell
Voice over : Lisa Hickey
Keywords: Urbanization